Dynastic Artists Who Made a Great Contribution to the Music of Uzbekistan - Shirinbekovna, Khasanova Nargiza (Research Parks Publishing LLC, 2023)
The article is devoted to music dynasties that made a great contribution to the art of Uzbek music, its role and importance in the traditions of the peoples of the East. Today, the study of this issue is widely studied not only by teachers but also by students. Eastern peoples with their rich historical heritage, worldview and centuries-old religious beliefs, dynastic traditions, spiritual and cultural values, which have been absorbed into the bright creations of folk craftsmen, unique lifestyles, scientists and artists. contributed greatly to its development and prosperity. The article discusses the bright representatives of the dynasties who contributed to the music art of Uzbekistan.